2021
DOI: 10.1111/joop.12344
|View full text |Cite
|
Sign up to set email alerts
|

How and when paradoxical leadership benefits work engagement: The role of goal clarity and work autonomy

Abstract: Paradoxical leadership behaviour (PLB) represents an emerging leadership construct that can help leaders deal with conflicting demands. In this paper, we report three studies that add to this nascent literature theoretically, methodologically, and empirically. In Study 1, we validate an effective short‐form measure of global PLB using three different samples. In Studies 2 and 3, we draw on the job demands–resources model to propose that paradoxical leaders promote followers’ work engagement by simultaneously f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 91 publications
2
53
1
3
Order By: Relevance
“…In response, this study examines paradoxical leadership as the antecedent of bootlegging. We did this on the basis that prior studies have indicated that this leadership-related factor can help employees to better understand, perform and improve their work tasks (Li et al , 2020; Nils et al , 2021; Zhang et al , 2015) and guide them to solve problems creatively (Li et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, this study examines paradoxical leadership as the antecedent of bootlegging. We did this on the basis that prior studies have indicated that this leadership-related factor can help employees to better understand, perform and improve their work tasks (Li et al , 2020; Nils et al , 2021; Zhang et al , 2015) and guide them to solve problems creatively (Li et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, paradoxical leaders attach great importance to work duty and requirements while allowing flexibility (Zhang et al , 2015). Clear job requirements with specific work goals and procedures can further help employees complete their job efficiently (Nils et al , 2021) and ensure they have more energy to think broadly beyond their roles. This leads to high levels of role breadth self-efficacy.…”
Section: Theoretical Development and Hypothesismentioning
confidence: 99%
“…Over the past decade, scholars have increasingly argued that leaders face contradictory challenges on a regular basis. This has led to the introduction of the concept of paradoxical leadership, which is reflected in the leader's ability to respond to paradoxes in a constructive way (Fürstenberg et al, 2021) and involves "practices seeking creative, both/and solutions that can enable fast-paced, adaptable decision making" (Lewis et al, 2014: 58). Zhang et al (2015) introduced the concept of paradoxical leader behavior to understand how seemingly competing, yet interrelated leader behaviors contribute to meeting competing workplace goals.…”
Section: Framing the Concept Of Paratoxical Leadershipmentioning
confidence: 99%
“…In general, paradoxical leadership is concerned with the effective handling of paradoxes that are inherent in leadership and/or organizations, whereas the key to effectiveness is seen in both/and rather than either/or approaches. Several studies provide empirical evidence that paradoxical leadership is associated with positive effects on followers, including employee creativity (Yang et al, 2021), employee voice behavior (Li et al, 2020), followers' in-role and innovative performance behaviors (Ishaq et al, 2021), work engagement (Fürstenberg et al, 2021), and organizational citizenship behavior (Pan, 2021). We therefore consider this line of research to represent the bright side of paradoxical leadership.…”
Section: Framing the Concept Of Paratoxical Leadershipmentioning
confidence: 99%
“…Undermining & support (Duffy, 2002;Nahum-Shani et al, 2014); Safety-specific transformational leadership & passive leadership (Mullen et al, 2011); Paradoxical leadership behavior (Zhang et al, 2015;Jia et al, 2018;Shao et al, 2019;Fürstenberg et al, 2021); Leader humility and narcissism (Owens et al, 2015;Zhang et al, 2017); Leader hypocrisy (Greenbaum et al, 2015); the research on Web of Science, and these keywords were ambivalence * AND leader * , inconsistency * AND leader * , paradox * AND leader * . We only focus on studies on the management field.…”
Section: Type Of Ambivalent Leader-follower Relationshipsmentioning
confidence: 99%